2009
DOI: 10.1080/10538710902901663
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Toward Sexual Offenders and Sex Offender Registration

Abstract: This study explores the relationship between fear of various types of sexual offenders and a belief that those sexual offenders should be subject to sex offender registration. We hypothesized that those who offend against children would elicit the most fear; consequently, the most feared offenders would be rated as most requiring registration. As part of a telephone survey, 733 participants answered questions about fear of sex offenders and agreement with requirements about registration for offenders convicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(165 citation statements)
references
References 17 publications
9
145
4
2
Order By: Relevance
“…The elevation of sexual crime as a key public policy issue since the latter part of the twentieth century has produced a range of social and justice system responses to sexual offending behavior, along with high levels of public support for these responses despite mixed findings regarding policy efficacy (Kernsmith, Craun, & Foster, 2009;Levenson, Brannon, Fortney, & Baker, 2007). Although previous literature has examined demographic and other correlates of public support for prevailing sexual offender management policies, there has been little research focus on the underlying psychological factors contributing to these levels of policy support (Anonymous, under review).…”
Section: Applying Moral Foundations Theory To Understanding Public VImentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of sexual crime as a key public policy issue since the latter part of the twentieth century has produced a range of social and justice system responses to sexual offending behavior, along with high levels of public support for these responses despite mixed findings regarding policy efficacy (Kernsmith, Craun, & Foster, 2009;Levenson, Brannon, Fortney, & Baker, 2007). Although previous literature has examined demographic and other correlates of public support for prevailing sexual offender management policies, there has been little research focus on the underlying psychological factors contributing to these levels of policy support (Anonymous, under review).…”
Section: Applying Moral Foundations Theory To Understanding Public VImentioning
confidence: 99%
“…(Harris & Socia, 2014, p. 2) To this general point, surveys that have prompted respondents to look beyond generalizations and to differentiate among various sexual offending scenarios, have found that levels of support for punitive measures may vary considerably based on situational, perpetrator, and victim characteristics. For example, Kernsmith et al, (2009) found that citizen beliefs about the appropriateness of subjecting an offender to community notification varied based on offense scenario. For example, 97% of respondents supported this procedure for adults who sexually abuse children, but only 65% found it suitable for a statutory rape case involving a 21-year-old perpetrator and a 16-year-old victim.…”
Section: Public Support For Sexual Offender Policiesmentioning
confidence: 99%
“…A recent study noted that individuals who report being fearful of any type of sex offender are most likely to support the sex offender registry (Kernsmith, Craun & Foster, 2009). Another study noted that most people have false beliefs about sex offenders.…”
Section: Public and Media Perception Of Sex Offendersmentioning
confidence: 99%
“…Gender -It appears that women hold more punitive attitudes to sexual offenders on both affective and behavioral measures than men (Kernsmith et al, 2009;Willis et al, 2013).…”
Section: Studymentioning
confidence: 99%